Robot-assisted Heller myotomy for achalasia - Giulia Fusi; Francesco Molinaro; Francesco Ferrara; Edoardo Bindi; Chiara Pellegrino; Chiara Calani; Mario Messina; Rossella Angotti (Elsevier, 2019)
Achalasia is a rare neuromuscular esophageal disorder in children. There are many surgical options to treatment including botulinum toxin (Botox) injections, oral pharmacologic therapies with nitrates and calcium channel blockers, pneumatic dilation (PD), and surgical myotomy (open surgery, endoscopy, laparoscopy and recently robotic approach). In pediatric age, usually, Heller's myotomy is the main choice. Laparoscopic approach is known and standardized. Few robotic have been published. We decided to report our first case to share our experience with scientific community. Keywords: Achalasia, Child, Dysphagia, Myotomy, Robotic surgery